Tinjauan Transaksi Transfer Dana Perbankan dalam Mengelola Risiko dan Mempertahankan Kepercayaan - Chiesa, Davina; S.T. Kansil, Christine (Dinasti Review Publisher, 2024)
The role of prudential banks in banking fund transfer transactions is a crucial aspect in maintaining financial system stability and public trust. Prudential banking entails a series of principles and actions designed to manage risks associated with fund transfers, including customer identification, monitoring suspicious transactions, and implementing anti-money laundering (AML) and counter-terrorism financing (CFT) procedures. Through the use of advanced technology and robust security systems, banks can mitigate the risks of fraud, money laundering, and terrorism financing in fund transfer transactions. The implementation of prudential banking principles not only ensures compliance with applicable banking regulations but also strengthens public trust in financial institutions. By maintaining integrity and transparency in every transaction, banks can enhance trust among customers and other stakeholders. Furthermore, prudential banking also plays a role in safeguarding the interests of the bank itself by minimizing loss risks and preserving the company's reputation